Perspectives of old-age and dementia researchers on communication with policymakers and public research funding decision-makers: an international cross-sectional survey - Fusdahl, Peter; Borda, Miguel Germán; Baldera, Jonathan Patricio; Aarsland, Dag; Khachaturian, Ara; Braut, Geir Sverre (Frontiers in Medicine, 2024)
IntroductionSociety commonly believes that research knowledge is complementary to public decision-making. This study aimed to understand the perspectives and implications of dementia researchers communicating with policymakers and public research decision-makers (public officials).MethodsThis study uses 24 questions from an anonymous, online survey, which was received by 392 members of nine European, Latin American, and United States medical researcher associations/networks in the fields of age-related neurological degeneration and dementia medicine. The data were analyzed via crosstab analysis, two group comparison analyses, and a logistic regression model.ResultsIn total, 91 (23.2%) respondents completed the questionnaire. Eight independent variables were related to researchers’ research discipline, research remuneration, experience, authorship, H-index, and research grants. The statistically significant variables determining whether the respondents had contact with public officials were “Years of research experience” (p = 0.004), “Number of articles first-authored in the last 5 years” (p = 0.007), and “Average H-index in the last 5 years” (p = 0.048) [median (IQR)]; 47% of the surveyed researchers had been in contact with public officials in the last 12 months. The most frequently communicated topics were the importance of their own research to society (61%) and their own funding (60%); 87% (n = 79) of the researchers did not believe that public officials had a very good understanding of their dementia research.ConclusionLess than half (47%) of dementia researchers communicate with public officials, and they communicate mostly about the importance of their own research and funding their own research. Nine of 10 researchers do not believe that public officials understand their research well.